2014
DOI: 10.1007/s00421-014-3032-5
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of exercise-induced spinal loop properties in response to oxygen availability

Abstract: This study investigated the effects of acute hypoxia on spinal reflexes and soleus muscle function after a sustained contraction of the plantar flexors at 40% of maximal voluntary isometric contraction (MVC). Fifteen males (age 25.3 ± 0.9 year) performed the fatigue task at two different inspired O₂ fractions (FiO₂ = 0.21/0.11) in a randomized and single-blind fashion. Before, at task failure and after 6, 12 and 18 min of passive recovery, the Hoffman-reflex (H max) and M-wave (M max) were recorded at rest and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 58 publications
2
23
0
Order By: Relevance
“…This partly differs from a previous report suggesting that a diminished O 2 availability in the brain could cause a failure of drive from the motor cortex during whole-body exercise ( Goodall et al, 2012 ), with the downregulation in quadriceps muscle recruitment under hypoxia limiting muscle fatigue ( Billaut et al, 2013 ). However, this is in line with the observation that hypoxia does not modify central regulation of motor drive during localized exercise involving a small muscle mass ( Rupp et al, 2015 ). EMG peak was maintained for the first 15 contractions in the current study despite an overall decrease in T peak and a lower SpO 2 in HYP, suggesting that the decrease in T peak was mainly due to peripheral fatigue with no or limited recruitment downregulation during maximal contractions.…”
Section: Discussionsupporting
confidence: 89%
“…This partly differs from a previous report suggesting that a diminished O 2 availability in the brain could cause a failure of drive from the motor cortex during whole-body exercise ( Goodall et al, 2012 ), with the downregulation in quadriceps muscle recruitment under hypoxia limiting muscle fatigue ( Billaut et al, 2013 ). However, this is in line with the observation that hypoxia does not modify central regulation of motor drive during localized exercise involving a small muscle mass ( Rupp et al, 2015 ). EMG peak was maintained for the first 15 contractions in the current study despite an overall decrease in T peak and a lower SpO 2 in HYP, suggesting that the decrease in T peak was mainly due to peripheral fatigue with no or limited recruitment downregulation during maximal contractions.…”
Section: Discussionsupporting
confidence: 89%
“…) or after fatiguing exercise in acute hypoxia (Rupp et al . ), it was reported that motoneurone excitability was not different from normoxia. However, each of these studies used a measure of motoneurone excitability (H‐reflex or F‐wave) that is less direct than the CMEP (McNeil et al .…”
Section: Introductionmentioning
confidence: 90%
“…To date, few studies have examined motoneurone excitability in hypoxia. At rest in both acute (Szubski et al 2006) and chronic hypoxia (Kayser et al 1993;Miscio et al 2009) or after fatiguing exercise in acute hypoxia (Rupp et al 2014), it was reported that motoneurone excitability was not different from normoxia. However, each of these studies used a measure of motoneurone excitability (H-reflex or F-wave) that is less direct than the CMEP (McNeil et al 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…Other investigations have reported that a fatigue‐related reduction in VA is greater when the availability of oxygenated blood is reduced (Amann et al., 2011; Sidhu et al., 2014). However, the exercise is typically prolonged or performed to exhaustion, meaning that there is substantial opportunity for greater metabolite accumulation (accompanied by enhanced group III/IV afferent feedback) owing to reduced availability of oxygenated blood (Goodall et al., 2010; Ruggiero et al., 2018; Rupp et al., 2012, 2015; Szubski, Burtscher, & Löscher, 2007). Given that the effect of hypoxia on the motor system appears to be heavily dependent on the duration of muscle activation and contraction task being performed, it is uncertain how VA of the elbow flexors is affected by brief and sustained isometric contractions in the presence of a constant exposure to hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…Given that descending drive to muscles is modulated by supraspinal and spinal circuits, several studies have profiled these areas of the nervous system in response to acute exposure to hypoxia. A variety of findings have been reported, with corticospinal excitability documented to increase (Goodall, Twomey, & Amann, 2014a; Ruggiero & McNeil, 2019), decrease (Goodall, Ross, & Romer, 2010) or show no change (Rupp, Racinais, Bringard, Lapole, & Perrey, 2015; Szubski, Burtscher, & Löscher, 2006, 2007) in response to hypoxic exposure. These equivocal findings might reflect methodological variations, whereby the duration of hypoxic exposure and the type of muscle activity that is examined can differ substantially between studies.…”
Section: Introductionmentioning
confidence: 99%